Estudio de factibilidad para la creación del museo del chagra, en la parroquia Machachi, cantón Mejía, provincia Pichincha - Jaguaco Cumbajín, Edison Danilo (2013)
This research proposes: conduct a feasibility study for the establishment of the museum in the Parish Chagra Machachi, Mejía Canton, Pichincha Province, this work was conducted through field work and primary and secondary information where the study was carried market surveys found that 96% of the inhabitants of the local population agrees with this project is implemented, whose services include: guidance and souvenir sales, and was established as museum visitors to the inhabitants of the population local profile of yourself and your needs. Technical study was developed which determined the size of the company, designing the production process flow chart, it will facilitate the provision of services from the client requests information until your visit, visiting six areas establishing and determining the costs technical area, in the environmental analysis was used Leopold proposed matrix, which determines that the activities to be performed are friendly to the environment, this provides the feasibility. In the administrative and legal study, we performed structural and functional organization, setting the area of marketing costs, the financial and administrative area. The economic study - financial, determining investments, income, expenses, financial statements. Finally for the evaluation of the project financial evaluation is performed: VAN, TIR, B/C and economic evaluation: contribution to economic growth, job creation and regional development. In conclusion, the project is feasible because in the social assessment will be half and will strengthen the cultural identity of the local population.